(untitled) (Journal of Mathematics Mechanics and Computer Science, 2019)
The need to develop an application format based on modern technologies is determined by the relevance of the optimal functioning of the environmental monitoring system. This system consists of several interacting modules. One of them is the "data assimilation module", which simulates the process using the data assimilation algorithm. For optimal modeling, you need source files in the Network Common Data Form (NetCDF) format, which will be generated from the developed application. The paper describes the characteristics, features, structure of the NetCDF format, presents the existing utilities and software, tools, visualization programs for working with this format. Their purpose, functions are analyzed. The generated NetCDF les are shown using the Scilab math program, which is an alternative to MATLAB. The paper presents a developed database of air pollutants. The structure of the main tables is described: fields, data type, field description, field properties. Database management system (DBMS) MS SQL is used for creating the database. The relational model of created database is presented. The interaction of the main components of the information-modeling system is shown.